THE IMPACT ON TURNOVER INTENTION THAT VIEWED THROUGH CAREER DEVELOPMENT AND WORK ENVIRONMENT WHICH MEDIATED BY WORK SATISFACTION AT PT. SINAR ANTJOL 1942 - Elsa Aprianis Marpaung; Singmin Johanes Lo (Dinasti International Journal of Education Management And Social Science, 2020)
This research aims to evaluated and analyzed those influence of career development and work environment towards turnover intention which mediated by employee work satisfaction at PT. Sinar Antjol 1942. This research was conducted from October 2019 to April 2020 at PT Sinar Antjol Jakarta. Research data was questionnaire that calculated by Slovin formula with sample of 120 respondents out of 170 employees who had standard error of 5%. Data were analyzed by SEM (Structural Equation Modeling) method with path analysis application SmartPLS (Partial Least Square) version 3.2.9 Windows. The results showed that career development and work environment had negative impact over turnover intention. Meanwhile, work satisfaction has succeeded in mediated between career development and work environment towards turnover intention.